2020
DOI: 10.1111/are.14528
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of bacterial community in a polyculture aquaculture system of Penaeus chinensis , Rhopilema esculenta and Sinonovacula constricta

Abstract: Polyculture with Chinese shrimp Penaeus chinensis, jellyfish Rhopilema esculenta and razor clam Sinonovacula constricta (S.J.R) is a common aquaculture system in Dandong, China. Investigation on the composition and function of microbial communities and their relationship with environmental factors in aquaculture systems have crucial implications. Therefore, the sequencing of 16S rRNA gene was applied to profile the bacterial community composition of water and sediment in S.J.R polyculture system in the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 82 publications
0
16
1
Order By: Relevance
“…Dai et al [22] has reported that nutrient levels all showed significant correlation with the microbial communities in pond water by studying aquaculture ponds from different areas in China. Moreover, T, pH, and DO were also positively correlated to the changes in microbial community composition, and they are reported to have strongly influence on bacterial growth and to contribute to ecosystem processes [31,32]. To further elucidate the driving environmental factors on special microbial taxa, we computed the Pearson correlation coefficient between the dominant genera and the environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al [22] has reported that nutrient levels all showed significant correlation with the microbial communities in pond water by studying aquaculture ponds from different areas in China. Moreover, T, pH, and DO were also positively correlated to the changes in microbial community composition, and they are reported to have strongly influence on bacterial growth and to contribute to ecosystem processes [31,32]. To further elucidate the driving environmental factors on special microbial taxa, we computed the Pearson correlation coefficient between the dominant genera and the environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…[128][129][130] As a result, the natural sedimentation of particulate matter produced by pelagic jellyfish can be employed to favour the culture of benthic and epibenthic organisms, such as clams, 107,108 shrimps 107,108 and sea cucumbers, 86 as these mainly feed on the organic matter available in the water column or sediment, not competing with jellyfish for food or space. [130][131][132] The polyculture of the Chinese shrimp Penaeus chinensis, with the jellyfish Rhopilema esculentum, and the razor clam Sinonovacula constricta is now commonly employed for the aquaculture of these important species in China, taking advantage of jellyfish to enhance the cycling of bioavailable carbon, nitrogen and phosphorous in the productive environment. 103,107,108,132 The oliver flounder fish Paralichthys olivaceus is also sometimes added to this type of polyculture systems with positive results.…”
Section: Jellyfis H For Feedmentioning
confidence: 99%
“…Indeed, aquaculture facilities whose effluents are rich in organic matter could benefit from the optimisation of this polyculture model using jellyfish, as this would allow farmers to improve nutrient use and increase revenues without additional production costs. 107,108,132 While further research is still required on the co-culture of jellyfish with other organisms to establish optimal culture densities for each species, as well as evaluate their interspecific interactions, its potential for large-scale aquaculture production is already well acknowledged. 78,86,103,107,131,132…”
Section: Jellyfis H For Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteobacteria was the most abundant and efficient colonizer in the polyculture and CON groups. In a polyculture aquaculture system of Penaeus chinensis , Rhopilema esculenta and Sinonovacula constricta , Proteobacteria was also the dominant phylum (Guan et al, 2020). Bacteroidetes and Proteobacteria were the most abundant phyla in water, sediment and crab intestine in iced fresh trash fish and formulated diet modes (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%